Impact of tank mixing plant hormones with bentazon and mesotrione on sweetpotato injury and weed control. Issue 3 (12th July 2021) - Caputo, Giovanni A.; Wadl, Phillip A.; McCarty, Lambert; Adelberg, Jeffrey; Saski, Christopher; Cutulle, Matthew
Abstract: Due to excessive crop damage, currently, there are no selective postemergent (POST) herbicides registered for sweetpotato [ Ipomoea batatas (L.) Lam] to control broadleaves and nutsedge species. Expansion of bentazon and mesotrione herbicide labels to include sweetpotato would be beneficial for growers. Two experiments were conducted. The first evaluated the dose response of sweetpotato cultivars Beauregard and Covington to bentazon (514, 1, 028, and 1, 542, g a.i. ha –1 ) and mesotrione (105, 210, and 315 g a.i. ha –1 ) when melatonin, 24‐epibrassinolide, or ascorbic acid (AsA) were included in the tank mix. The second experiment evaluated the efficiency of bentazon and mesotrione for control of yellow nutsedge ( Cyperus esculentus L.) and Palmer amaranth ( Amaranthus palmeri S. Wats.), when different doses of melatonin, 24‐epibrassinolide, or AsA were added to each herbicide. In the first experiment, when treated with herbicide alone, Beauregard exhibited injury levels lower than Covington for both herbicides. No injury was observed when plants were treated with plant hormones or AsA alone. At the lowest dose of bentazon and mesotrione, the addition of AsA or plant hormones in the tank mix significantly reduced percentage injury and increased plant tolerance, requiring higher doses of herbicide to cause 10, 20, and 30% injury. In the second experiment, the addition of plant hormones and AsA in the tank mix had no antagonistic effect on herbicide effectiveness, exhibiting similar levels of injuries as herbicides application alone. These results suggest that the use of plant hormones and AsA could improve sweetpotato tolerance to POST applications of bentazon and mesotrione without reducing herbicide effectiveness. Core Ideas: Plant hormones and ascorbic acid improved herbicide tolerance in sweetpotatoes. No antagonistic interaction between plant hormones and herbicides was found in controlling weeds. Tank mix of herbicide and plant hormones could enable the use of postemergent herbicides in sweetpotato.